2010
DOI: 10.1016/j.cmet.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic-Specific Disruption of SIRT6 in Mice Results in Fatty Liver Formation Due to Enhanced Glycolysis and Triglyceride Synthesis

Abstract: Under various conditions mammals have the ability to maintain serum glucose concentration within a narrow range. SIRT1 plays an important role in regulating gluconeogenesis and fat metabolism; however, the underlying mechanisms remain elusive. Here we show that SIRT1 forms a complex with FOXO3a and NRF1 on the SIRT6 promoter and positively regulates expression of SIRT6, which in turn negatively regulates glycolysis, triglyceride synthesis and fat metabolism by deacetylating histone H3 lysine 9 in the promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
414
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 442 publications
(448 citation statements)
references
References 46 publications
27
414
2
5
Order By: Relevance
“…SIRT6 was shown to negatively control the mRNA expression of glycolytic and lipogenic genes (16,32). This observation is strikingly similar to the decreased mRNA levels of pyruvate kinase (PK) and fatty acid synthase (FAS) that are reported with PUFA treatment in primary hepatocytes (33).…”
Section: The Corresponding O-[supporting
confidence: 64%
“…SIRT6 was shown to negatively control the mRNA expression of glycolytic and lipogenic genes (16,32). This observation is strikingly similar to the decreased mRNA levels of pyruvate kinase (PK) and fatty acid synthase (FAS) that are reported with PUFA treatment in primary hepatocytes (33).…”
Section: The Corresponding O-[supporting
confidence: 64%
“…According to our data, we speculate that down-regulation of the Pcsk9 gene expression may be responsible for the low LDL-cholesterol phenotype in the Sirt6 transgenic mice. Additionally, Sirt6 also significantly represses fatty acid and cholesterol biosynthetic genes and activates fatty acid oxidation genes (38,43). Apparently, Sirt6 has a salutary effect on lipid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Because Sirt6 is decreased in the livers of obese animals and humans (38,48), it implicates a potential consequence for the development of hypercholesterolemia, particularly high LDL-cholesterol. Previously, it was reported that systemic overexpression of Sirt6 in mice can lower LDLcholesterol under conditions of either chow or high fat diet; however, the underlying mechanism is not clear (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the role of Sirtuins in aging stem cells will likely provide insights into the mechanisms that regulate stem cell homeostasis, particularly in response to stress stimuli. In addition, the ability of Sirtuins to regulate both organismal energy metabolism (Banks et al, 2008;Feige et al, 2008;Kim et al, 2010;Ramadori et al, 2010;Zhong et al, 2010) and chromatin may be particularly important for the response of adult stem cells to environmental stimuli such as dietary restriction that are known to promote longevity and delay signs of aging.…”
Section: Histone Acetylation In Aging Stem Cellsmentioning
confidence: 99%